Numerical Study of Failure Modes and Crack Propagation in 2A12 Aluminum Target against Blunt-Nosed Projectile at Low Yaw Angle - Deng, Y.F.; Li, J.F.; Jia, B.H.; Wei, G. (Проблемы прочности, 2016)
Simulation models of 2A12 aluminum targets with thickness 1mm stricken by the high strength 38CrSi blunt-nosed projectiles at different yaw angle have been established with the help of ABAQUS, then the failure mode and crack propagation of target was analyzed after the effectiveness of simulation models had been verified by experiment, also the motion and angle variation of projectile was studied. Выполнено численное моделирование с помощью вычислительного пакета ABAQUS ударного взаимодействия мишени толщиной 1 мм из алюминиевого сплава 2А12 со снарядом из высокопрочной стали 38CrSi с затупленной носовой частью при малых углах атаки. После экспериментальной проверки эффективности разработанных моделей проанализированы типы разрушения и роста трещин в мишени с учетом последующего движения и изменения угла атаки снаряда. Виконано числове моделювання за допомогою обчислювального пакета АВАQUS ударної взаємодії мішені товщиною 1 мм з алюмінієвого сплаву 2А12 зі снарядом із високоміцної сталі 38CrSi, що має затуплену носову частину, за малих кутів атаки. Після експериментальної перевірки ефективності розроблених моделей проаналізовано типи руйнування та росту тріщин у мішені з урахуванням наступного руху і зміни кута атаки снаряда.